Improving Bahasa Indonesia writing skill: a project-based learning experimental study - Kurniati, Lisdwiana; Syaputri, Wuri; Efendi, Yudi; Tussolekha, Rohmah; Saputry, Dessy (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study examines the effectiveness of project-based learning (PBL) in improving the academic writing skills of sixth-semester Bahasa Indonesia students at Universitas Muhammadiyah Pringsewu. We used a quasi-experimental design to address on the effects of PBL on improving Bahasa Indonesia wtiting skill among university students. This involved 32 students participating in PBL activities for one semester. Pre- and post-intervention tests measured writing quality, engagement, and critical thinking skills. Statistical studies demonstrated a notable enhancement in writing quality after the intervention, as shown by paired t-tests (???? < 0.05). Additionally, groups that participated in various problem-based learning (PBL) activities had higher levels of engagement, as indicated by ANOVA (???? < 0.05). The examination of observations and reflective essays revealed several prominent themes, including heightened passion, improved critical thinking, and a higher drive to learn and use Bahasa Indonesia. The study's findings indicate that Problem-Based Learning (PBL) is a potential method to improve the competency of university students in Bahasa Indonesia. PBL encourages greater involvement and the development of skills in the language. Practically, Project-Based Learning (PBL) enhances students' writing skills and promotes a profound comprehension of language by offering genuine learning experiences and chances for collaborative inquiry. This approach encourages students to actively participate in language usage in real-world situations. These findings add to the wider discussion on innovative teaching methods in higher education and have implications for developing curriculum and instructional practices that aim to enhance educational results.